Targeting SRSF1 improves cancer immunotherapy by dually acting on CD8+T and tumor cells - Gui-Qi Zhu; Zheng Tang; Tian-Hao Chu; Biao Wang; Shi-Ping Chen; Chen-Yang Tao; Jia-Liang Cai; Rui Yang; Wei-Feng Qu; Yi Wang; Qian-Fu Zhao; Run Huang; et al. (Signal Transduction and Targeted Therapy)
Abstract Serine arginine-rich splicing factor 1 (SRSF1) is a key oncogenic splicing factor in various cancers, promoting abnormal gene expression through post-translational regulation. Although the protumoral function of SRSF1 is well-established, the effects of inhibiting tumor-intrinsic SRSF1 on the tumor microenvironment and its impact on CD8+ T cell-mediated antitumor immunity remain unclear. Our findings indicate that depleting SRSF1 in CD8+ T cells improve antitumor immune function, glycolytic metabolism, and the efficacy of adoptive T cell therapy. The inactivation of SRSF1 in tumor cells reduces transcription factors, including c-Jun, c-myc, and JunB, facilitating glycolytic metabolism reprogramming, which restores CD8+ T cell function and inhibits tumor growth. The small-molecule inhibitor TN2008 targets SRSF1, boosting antitumor immune responses and improving immunotherapy effectiveness in mouse models. We therefore introduce a paradigm targeting SRSF1 that simultaneously disrupts tumor cell metabolism and enhances the antitumor immunity of CD8+ T cells.